The effect of profitability, financial distress, debt default, audit client tenure, audit lag on going concern audit opinion - Budiantoro, Harry; Listriyani, Listriyani; Oktavia, Dinda; Ningsih, Hestin Agus Tantri; Primadini, Adinda (Jurnal Akuntansi dan Manajemen, 2025)
This study investigates the impact of profitability, financial distress, debt default, audit client tenure, and audit lag on going concern audit opinions. The research focused on 46 manufacturing companies across various industrial sectors listed on the Indonesia Stock Exchange from 2019 to 2023, with 24 companies selected as research samples. A quantitative associative method was employed for the research, using purposive sampling for participant selection. The data analysis involved descriptive statistical analysis, logistic regression analysis, and hypothesis testing through the Wald test (partial t-test) and the determination test. The findings reveal that profitability has a significant adverse effect on going concern audit opinions. In contrast, financial distress and debt default have a significantly positive impact on going-concern audit opinions. However, audit client tenure and audit lag do not considerably affect going concern audit opinions. The managerial implications suggest that company management should pay closer attention to profitability, financial health, and debt management to avoid receiving a going concern audit opinion, which could potentially undermine investor confidence.